Direct leach approaches to Platinum Group Metal (PGM) ores and concentrates: A review - Mpinga, C.; Eksteen, Jacques; Aldrich, Chris; Dyer, L. (Elsevier Ltd, 2015)
Platinum Group Metals (PGMs), often with associated gold, have very few occurrences where they are present in an ore deposit at economically extractable levels. They are classified as both precious and critical metals due to their scarcity and their wide industrial use. With deteriorating socio-political environments in most primary PGM producing countries, PGM deposits that are smaller but in less risky jurisdictions have to be evaluated. However, the lower PGM grades, increased mineralogical complexity of the ores, capital intensity and strict environmental regulations in other international jurisdictions, limit the implementation of conventional metallurgical processing options, particularly smelter-based operations. The conventional smelter-based process options are justifiable for high grade, low chromite, large resource and long life-of-mine operations. In the present paper, we review some of the most recent literature on the predominantly hydrometallurgical approaches to PGM extraction. A number of metallurgical processes that generate either a PGM rich leachate or a residue containing metal values, and the various methods in use for their recoveries from pregnant rich solutions are reviewed. Sixteen process flowsheet variants combining conventional and proprietary unit process technologies are provided, and their process chemistries and key technical operating parameters are compared. Where appropriate, the key thermodynamic and kinetic factors are given and compared.